Highly Efficient Simulated Solar Light‐Driven Photocatalytic Degradation of 4‐Nitrophenol over CdS/Carbon/MoSx Hybrids. Issue 63 (11th October 2021) - Kostelenos, Konstantinos; Bairamis, Feidias; Karamoschos, Nikolaos; Sygellou, Lamprini; Andrikopoulos, Konstantinos S.; Konstantinou, Ioannis; Tasis, Dimitrios
Abstract: Among the various organic pollutants and industrial chemicals, 4‐nitrophenol has been one of the most monitored substances in aqueous environments, due to its enhanced solubility in such systems. This research reports for the first time the microwave‐assisted synthesis of CdS/carbon/MoSx hybrids and the subsequent utilization of such systems as photocatalysts for 4‐nitrophenol degradation. The hybrids demonstrated a variable photocatalytic activity, by using a variety of organic substances as precursors for the solvothermal carbonization step. By using ascorbic acid as precursor, the corresponding ternary composite exhibited excellent photocatalytic activity, with the 4‐nitrophenol concentration been almost quantitatively decayed within 45 min of irradiation. This could be ascribed due to the generation of a high population of heterojunctions as well as the chemical speciation of Mo‐based nanostructures. Such ternary hybrids may be utilized as potential photocatalytic systems in processes, where removal of toxic water‐soluble substances is the key issue. Abstract : A novel photocatalytic system is readily synthesized through a microwave‐assisted hydrothermal process. The CdS/MoSx heterojunction using ascorbic acid‐derived carbon as cocatalyst degrades 4‐nitrophenol about 9 times faster than neat CdS. The enhancement of photocatalytic activity towards the degradation of an organic pollutant originates from efficient charge separation in the formed heterojunctions.